2014
DOI: 10.3390/ijerph110302899
|View full text |Cite
|
Sign up to set email alerts
|

Association of Uric Acid with Metabolic Syndrome in Men, Premenopausal Women and Postmenopausal Women

Abstract: Objective: To explore the relationship between serum uric acid (SUA) and metabolic syndrome (MS) in men, premenopausal women and postmenopausal women. Methods: A cross-sectional study was conducted in 1,834 community-based Southern Chinese participants from June to October 2012. Sex-specific SUA quartiles were used as follows: <345, 345–<400, 400–<468, ≥468 µmol/L in males; and <248, 248–<288, 288–<328, ≥328 µmol/L in females. MS was defined by the National Cholesterol Education Program Adult Treatment Panel I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 36 publications
1
28
1
3
Order By: Relevance
“…In line with previous studies [21][22][23] we reported higher serum uric acid level in women with MetS, comparing to those without MetS. Moreover, in a prospective study conducted by Zurlo et al [24] high serum uric acid levels significantly and independently predicted MetS in older women, but not in men, over a 4.4-year follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous studies [21][22][23] we reported higher serum uric acid level in women with MetS, comparing to those without MetS. Moreover, in a prospective study conducted by Zurlo et al [24] high serum uric acid levels significantly and independently predicted MetS in older women, but not in men, over a 4.4-year follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…[1–5] Several epidemiologic studies showed that serum urate (SU) levels were lower in cigarette smokers than non-smokers. [611] Only one recent publication from the Framingham Heart Study (FHS) cohort has examined the association between smoking and risk of gout and reported a lower risk of gout among smokers, only in men but not in women. [12] However, information on dose and duration of smoking was not available in the FHS.…”
mentioning
confidence: 99%
“…Birçok çalışmada yüksek serum ÜA seviyelerinin, KVH risk faktörleri, KVH ve KVH progresyonu ile ilişkili olduğu gösterilmiştir [3][4][5][6]. Serum ÜA ile obezite, dislipidemi, hipertansiyon, bozulmuş glukoz metabolizması gibi KVH risk parametrelerinin ilişkisini açıklamak için birçok sebep ileri sürülmüştür.…”
Section: Discussionunclassified